The Correlation between Single-Nucleotide Polymorphisms in Genes of Lysosomal and Proteasomal Proteolysis and Their Impact on the Effectiveness of Asthma Treatment in Children - O.V. Iemets (Zaslavsky O.Yu., 2016)
Purpose. To detect the correlation between single-nucleotide polymorphisms rs510432 in gene ATG5 and rs4769628 in gene POMP, to determine combination of allelic variations at high risk of atopic diseases. To evaluate the impact of allelic variations of above-mentioned gene on the effectiveness of bronchial asthma treatment in children. Materials and methods. To determine the correlation between single-nucleotide polymorphisms in gene ATG5 and РОМР, we have used the method of multifactor dimensionality reduction. To assess the effectiveness of asthma therapy, a 5-point scale test for asthma control was applied. We evaluated the dynamics of total score of asthma controllability 12 weeks after administration of standard therapy in children depending on the allelic variants of rs510432 in gene ATG5 and rs4769628 in gene POMP. Results. Polymorphisms rs510432 in gene ATG5 and rs4769628 in gene POMP have antagonistic interaction. The high risk of atopic diseases is detected in such combinations: heterozygous (CT) or minor (TT) genotype of ATG5 gene in combination with heterozygous (AG) or major (AA) genotypes of gene POMP. During standard therapy for 12 weeks, the average score of total asthma controllability was significantly higher in patients with major and heterozygous variants of rs510432 polymorphism in gene ATG5 than in patients with minor genotype (p < 0.05). In patients with heterozygous genotype AG rs4769628 in gene POMP, the average score of total asthma controllability was significantly higher than in children with major variant of AA genotype (p < 0.05). Conclusions. We have identified combinations of allelic variations rs510432 of gene ATG5 and rs4769628 in gene POMP associated with a high risk of atopic diseases in children. The average score of total asthma controllability depends on polymorphisms rs510432 in gene ATG5 and rs4769628 in gene POMP.